2018
DOI: 10.1098/rspb.2018.1746
|View full text |Cite
|
Sign up to set email alerts
|

Building the differences: a case for the ground tissue patterning in plants

Abstract: A key question in biology is to understand how interspecies morphological diversities originate. Plant roots present a huge interspecific phenotypical variability, mostly because roots largely contribute to adaptation to different kinds of soils. One example is the interspecific cortex layer number variability, spanning from one to several. Here, we review the latest advances in the understanding of the mechanisms expanding and/or restricting cortical layer number in Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…For root length measurements, plates were photographed and the resulting images were analyzed using the analysis software ImageJ 1.47v available online (https://imagej.nih.gov/ij/). Root meristem size of 5 days post germination plants was measured based on the number of cortex cells in a file extending from the quiescent center to the first elongated cortex cell excluded, as described previously [38][39][40]. Images were obtained using a confocal laser scanning microscope (Zeiss LSM 780).…”
Section: Root Length Meristem Size and Cell Size Analysismentioning
confidence: 99%
“…For root length measurements, plates were photographed and the resulting images were analyzed using the analysis software ImageJ 1.47v available online (https://imagej.nih.gov/ij/). Root meristem size of 5 days post germination plants was measured based on the number of cortex cells in a file extending from the quiescent center to the first elongated cortex cell excluded, as described previously [38][39][40]. Images were obtained using a confocal laser scanning microscope (Zeiss LSM 780).…”
Section: Root Length Meristem Size and Cell Size Analysismentioning
confidence: 99%
“…SHR moves toward the CEID, CEI and endodermis via plasmodesmata, where it is sequestered into the nucleus [22,23] (Figure 2 and Figure 3). SHR movements restriction is fundamental for GT patterning, as overexpression of SHR results in additional GT layer formation [24,25]. In the vasculature, SHR is maintained mostly in the cytoplasm by the activity of SCARECROW-LIKE23 (SCL23) [26].…”
Section: Root Radial Axismentioning
confidence: 99%
“…It was recently shown that SHR, together with SCR, also specifies endodermis differentiation. Functional endodermis is characterized by Casparian strips, lignified structures deposited on the radial and transverse side of the endodermal cell wall [24]. SHR directs the formation of the Casparian strips by inducing the MYB DOMAIN transcription factor MYB36 and the receptor-like kinase SGN1 and SGN3 [50,51] (Figure 3).…”
Section: Root Radial Axismentioning
confidence: 99%
See 2 more Smart Citations